Skin Disease Detection Based on Image Processing Techniques - Farhin, J. Reshma; Omprasanth, G.; Priya, N.; Rakshan, K. R. (European Journal of Life Safety and Stability (2660-9630), 2022)
The expansion of versatile applications makes it more straightforward for people to get exceptional data. Clients are looking for a response from the virtual world, including medical issues. This framework talks about the portable use of skin illness identification because of the picture. The framework requires a dataset of undesirable skin pictures. This framework is intended to identify skin illness from unfortunate pictures. Preprocessing of the pictures will be looked at by observing the distinction in edge esteem. The distinction in limit worth will be advanced in the decision-production against thought undesirable skin that is being recognized. The application worked with Android Studio with an Open CV library to execute the SVM (support vector machine). Android-based portable applications have been effectively made, and they can recognize the skin illnesses picture. In any case, given recognition, it gives an idea of the sickness.